If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-10=5(x+9)
We move all terms to the left:
-10-(5(x+9))=0
We calculate terms in parentheses: -(5(x+9)), so:We get rid of parentheses
5(x+9)
We multiply parentheses
5x+45
Back to the equation:
-(5x+45)
-5x-45-10=0
We add all the numbers together, and all the variables
-5x-55=0
We move all terms containing x to the left, all other terms to the right
-5x=55
x=55/-5
x=-11
| 5+4f-5f=f-7 | | 12x-8=-4+24 | | 0.3x-6.2=3.5 | | (x+12)=(5x-32) | | 7n+23+4n=59 | | (2w+10)w=310 | | 4(x+3=5x+9 | | –7t=5.6 | | R(x)=9x | | 10+4u=2u−10+7u | | -3(6+n)-6n=63 | | 4x18=x-3 | | (x-28)+(x-28)+40=180 | | (2)=x+5 | | 16+19m-6=19m-17 | | 3.5=6.2-0.3x | | n=3/5 | | 0.5(x-6)=18 | | 2x-9+9x=11x | | 31n=-63 | | (x-30)+(x-30)+40=180 | | 5r-3=11+2r-7+8 | | 35÷n=7 | | -4q-8=-2q+4 | | 12x-30+3x=42 | | -5(w-8=3w-32 | | -5k-20=-5k+11 | | -31n=-63 | | (x+19)=(5x-37) | | A=5/4(h-71) | | 0.5*(x-6)=18 | | -23+7x=5 |